Jews and Palestinians in the late Ottoman era, 1908-1914 : claiming the homeland - Fishman, Louis A. (Edinburgh studies on the Ottoman Empire., 2020)
Uncovering a history buried by different nationalist narratives (Jewish, Israeli, Arab and Palestinian) this text looks at how the late Ottoman era set the stage for the on-going Palestinian-Israeli conflict.